PENGARUH PROFESIONALISME, AKUNTABILITAS DAN INTEGRITAS TERHADAP KUALITAS AUDIT BADAN PEMERIKSAAN KEUANGAN (BPK) RI PERWAKILAN PROVINSI RIAU - Tri Indah Maya Sari; Andreas -; Lila Anggraini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this study is to obtain empirical evidence of Professionalism, Accountability, and Integrity to auditor quality. Study is warm up finance examiners (BPK-RI) is Riau provision. Respondents in this research is the auditors who work in finance examiners. Method using a questionnaire with the number of auditors that the sample of this research was 55 auditors work in finance examiners. Data were analyzed with Multiple Regression and Moderate Regression Analysis-MRA. The results showed that the presence of a direct effect of Professionalism, Accountability, and Integrity on the Audit Quality. Analysis using The coefficient of determination (R2) shows that jointly variables Professionalism, Accountability, and Integrity on the Audit Quality amounted to 30,3%.Keywords: Professionalism, Accountability, and Integrity on the Audit Quality.